Comparative prognostic value of myocardial strain derived from DENSE CMR: the British Heart Foundation MR-MI study. (23rd February 2017) - Mangion, Kenneth; Carrick, David; Carberry, Jaclyn; Mahrous, Ahmed; McComb, Christie; Gao, Hao; Luo, Xiayou; Oldroyd, Keith; Eteiba, Hany; McEntegart, Margaret; Lindsay, Mitchell; Petrie, Mark; et al.
Abstract: Background: Infarct size assessed early after acute ST-segment elevation myocardial infarction (STEMI) can overestimate the true extent of infarction, limiting its usefulness as a prognostic biomarker. Myocardial strain derived from displacement encoding with stimulated echoes (DENSE) cardiovascular magnetic resonance (CMR) provides information on myocardial contractility with high precision and accuracy. We hypothesised that the prognostic value of peak circumferential strain is higher than infarct size. Methods: In a prospective, single centre study, participants underwent 1·5T CMR 2 days and 6 months after myocardial infarction. The 5-SD technique was used to quantify late gadolinium enhancement (LGE) as proportion of left ventricular mass. Mid-left ventricular DENSE acquisitions were analysed using postprocessing software. During longer-term follow-up, major adverse cardiac events (MACE) were independently assessed by masked cardiologists. Participants provided written informed consent and ethics approval was given (reference 10/S0703/28). This study is registered withClinicalTrials.gov, numberNCT02072850 . Findings: 300 patients underwent CMR (mean age 58·6 years [SD 13·2], 237 men [79%], 118 anterior myocardial infarction [39%], 30 with diabetes [10%], 284 with normal flow [Thrombolysis in Myocardial Infarction grade 3] after percutaneous coronary intervention [95%]). 259 of these patients had DENSE acquired, of whom 21 (8%) experienced a MACE at 3 years' follow-up. DENSE and baseline LGE had reasonable power for prediction of adverse events (area under the curve [AUC] DENSE 0·712, p=0·001; AUC LGE 0·644, p=0·028). For MACE (receiver operating characteristic analysis), optimal cut-offs for peak circumferential strain using DENSE was −10·51%, and LGE 24·05 g. Cox-regression analysis showed that DENSE (hazard ratio 1·175, 95% CI 0·036–1·334; p=0·012) offered an incremental prognostic benefit over LGE (1·040, 1·010–1·070; p=0·008) to predict MACE. Interpretation: DENSE-derived peak circumferential strain offers an incremental prognostic benefit over infarct size revealed by LGE to predict MACE; a cut-off of −10·51% can identify STEMI patients at higher risk of events. This is the first time, to our knowledge, that CMR-derived strain has been shown to provide prognostic utility in patients with STEMI. Funding: This research was supported by project grants from the Chief Scientist Office (SC01), Medical Research Scotland (343 FRG), and the British Heart Foundation (BHF-PG/14/64/31043).